Motricidad fina y su desarrollo en la pre-escritura de enseñanza y aprendizaje, de los estudiantes del 2º año de la escuela de educación general básica, Lizardo García Avilés, recinto Lechugalito, Parroquia Zapotal, cantón Ventanas, Provincias Los Ríos - Monserrate Bolaños, Alba Maritza (2020)
Motor skills are complemented by material elements of the classroom to teach; also, that anecdotes are a motrite option in teaching, in the classroom and an acting stage. There is a matter for the teacher who has been educated from the academic in the face of his social, cultural and family formation, which makes this possible other forms of Fine Motor and its development is an obligation of the state, but also of the family and society, where the school is one of the institutions of greatest incidence and where teachers as educational agents have the task of advancing intentional, relevant and timely educational processes generated from the interests, characteristics and capabilities of the students, we raise the present research, whose main objective is to demonstrate what elements of the modeling technique contribute to the development of fine motor skills in the pre-writing of teaching and learning, and in turn improves the initial writer process of the students of the 2nd year of Basic General Education of the School "Lizardo García Avilés", and at the same time the motor skills in the pre-school writing that has developed. Fine motor skills of children through the exercises of methodological strategies applied to students of the school, for this purpose, information relevant to the verification of the hypothesis and the establishment of conclusions and recommendations are collected lead to proposing solutions to the problem identified, the same one that allows authorities, teachers and students to reflect on ahí this research and the feasibility of the proposal, in order to improve the level of education and that the contents of these activities respond to educational needs and requirements which is to develop "Methodological strategies for the development of pre-writing in basic second-grade students".